2003
DOI: 10.1029/2002ja009500
|View full text |Cite
|
Sign up to set email alerts
|

A multidiagnostic investigation of the mesospheric bore phenomenon

Abstract: [1] Imaging measurements of a bright wave event in the nighttime mesosphere were made on 14 November 1999 at two sites separated by over 500 km in the southwestern United States. The event was characterized by a sharp onset of a series of extensive wavefronts that propagated across the entire sky. The waves were easily visible to the naked eye, and the entire event was observed for at least 5 1 2 hours. The event was observed using three wide-angle imaging systems located at the Boston University field station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
198
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(236 citation statements)
references
References 40 publications
(76 reference statements)
28
198
3
Order By: Relevance
“…These observational facts lead us to believe that the front should be a mesospheric bore suggested by Dewan and Picard (2001), which is: the presence of an extended bright front, followed by short wavelength wave trains and the presence of wave ducting condition. Several previous works have used the same criteria (Medeiros et al, 2001Smith et al, 2003Smith et al, , 2005She et al, 2004;Fechine et al, 2005). A similar mesospheric wave front has also been observed by Swenson et al (1998).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These observational facts lead us to believe that the front should be a mesospheric bore suggested by Dewan and Picard (2001), which is: the presence of an extended bright front, followed by short wavelength wave trains and the presence of wave ducting condition. Several previous works have used the same criteria (Medeiros et al, 2001Smith et al, 2003Smith et al, , 2005She et al, 2004;Fechine et al, 2005). A similar mesospheric wave front has also been observed by Swenson et al (1998).…”
Section: Discussionmentioning
confidence: 54%
“…The occurrence of this sort of event would be associated with a temperature inversion layer that Correspondence to: A. F. Medeiros (afragoso@df.ufcg.edu.br) acts as a wave duct. Smith et al (2003) and She et al (2004) first reported simultaneous occurrence of the mesospheric bore and temperature inversion layer. Since then it has been recognized that the inversion layer could play an important role in the formation of the mesospheric bore.…”
Section: Introductionmentioning
confidence: 98%
“…Many DNB-observed nightglow wave features have no obvious ties to lower atmospheric forcing (e.g., produce a readily identifiable signature in nightglow emissions (47). From a surface observer's perspective, the visual appearance of a bore's passage entails a sudden brightening of the night sky (the "bright night" effect; 48), followed by a sharp wave front associated with the hydraulic jump, and finally a series of linearly oriented alternating bright and dark bands (49). This trailing wave pattern, the bore's principle mechanism for energy dissipation, is phase-locked to the hydraulic jump.…”
Section: Suomi Makes a Splash With Global Nightglow Imagerymentioning
confidence: 99%
“…The highly curved nature of the wave fronts indicates that the source region was relatively localized and nearby, but a search of limited meteorological data on that night was not conclusive. Far more dramatic was the passage of the mesospheric bore event on 22 August 2001 (lower panel) that resulted in a strong reduction in the O( 1 S) emission brightness due to an upward displacement in the O( 1 S) layer height (Taylor et al, 1995;Smith et al, 2003). More thorough studies of mesospheric dynamics will be possible with a new detector installed at El Leoncito in early 2006, together with additional diagnostics systems from collaborating scientists.…”
Section: Airglow Structures Associated With Mesospheric Dynamicsmentioning
confidence: 99%